Autologous platelet-rich plasma infusion improves clinical pregnancy rate in frozen embryo transfer cycles for women with thin endometrium. Issue 3 (January 2019) - Chang, Yajie; Li, Jingjie; Wei, Li-na; Pang, Jiahui; Chen, Jianhui; Liang, Xiaoyan
Abstract: Background: Adequate thickness of the endometrium has been well recognized as a critical factor for embryo implantation. This was a prospective cohort study to investigate the benefits of platelet-rich plasma (PRP) for women with thin endometrium who received frozen embryo transfer (FET) program in a larger number of patients and explore the underlying mechanism. Methods: In this study, we investigated the effects of PRP in women with thin endometrium in FET program. 64 patients with thin endometrium (<7 mm) were recruited. PRP intrauterine infusion was given in PRP group during hormone replacement therapy (HRT) cycle in FET cycles. Results: After PRP infusion, the endometrium thickness in PRP group was 7.65 ± 0.22 mm, which was significantly thicker than that in control group (6.52 ± 0.31 mm) ( P  <.05). Furthermore, PRP group had lower cycle cancellation rate when compared to control group (19.05% vs. 41.18%, P  <.01). The implantation rate and clinical pregnancy rate in PRP group were significantly higher than those in control group (27.94% vs 11.67%, P  <.05; 44.12% vs 20%, P  <.05, respectively). PRP blood contained 4 folds higher platelets and significantly greater amounts of growth factors including platelet-derived growth factor (PDGF)-AB, PDGF-BB, and transforming growth factor (TGF)- β than peripheral blood ( P  <.01). Conclusions: PRP plays a positive role in promoting endometrium proliferation, improving embryo implantation rate and clinical pregnancy rate for women with thin endometrium in FET cycles.